Potensi Wilayah Kota Bukittinggi dalam Pengembangan Usaha Ternak Sapi Potong dan Kontribusinya Terhadap Pendapatan Keluarga - Yetmaneli Yetmaneli (Jurnal Peternakan Indonesia (Indonesian Journal of Animal Science), 2007)
The aims of the present research were to determine local base resources of Bukittinggi city for beef cattle raising especially feed lot fattening and determine contribution of beef cattle raising on familiy income. Both secondary and primer data was used quitioner was main instrumen for data gathering. Thirty eight cattle raiser was intervied with was divided into three strata, base on amount of cattle was raised. Benefit cost analysis was used to determined familiy income in cattle raising. The result study shawn that the first: Bukittinggi city has several advantages for beef cattle raising (feed lot fattening) namely: climate, topografy,marketing aspect, institutinal and local government policy. As well as availability of feed, water, labor force, medicine and tecnology. The second beef cattle raising (feed lot fattening) has contributed 18,09%, 24,67%, 57,41% respectively strata I, II, III toward family income.